FRI0432 Single-port thoracoscopic sympathicotomy for treatment resistant raynaud's phenomenon. first report of a novel minimally-invasive endoscopic technique. (12th June 2018) - Van Roon, A.; Kuijpers, M.; Eman Abdulle, A.; Van de Zande, S.; Mariani, M.; Bos, R.; Klinkenberg, T.; Bootsma, H.; Smit, A.; Mulder, D.J.
Abstract : Background: Raynaud's phenomenon of the hands is a great burden in daily life and reduces quality of live in patients with or without an underlying connective tissue disease. Although vasodilatory treatment may be effective in some patients, complaints may be resistant to treatment, for which additional treatment options are very limited. In earlier years, thoracic sympathectomy by anterior or axillary thoracotomy has been shown effective, but with a great surgical burden and limited durability. In the 90 s, endoscopic procedures were introduced. However, these techniques needed multiple endoscopic ports and still performed a relatively mutilating sympathectomy of the sympathetic ganglia. In our centre, the single-port thoracoscopic sympathicotomy (SPTS) was developed, which is a new minimally invasive endoscopic technique with a limited surgical burden. Objectives: The aim of the current pilot study was to evaluate feasibility and efficacy of SPTS in patients with treatment resistant Raynaud's. Methods: This new technique entails only a single-port endoscopic procedure, during which a sympathicotomy (figure 1) of the nerve is performed, thus sparing the ganglia. Hospital stay is limited to one day. The procedure has been developed for treatment of hyperhidrosis and performed in our hospital in over 550 patients without major adverse events with a success rate of 98%. In the current study, we aim to include 10 patients with treatment resistant Raynaud's, defined as unsatisfactory effect or contraindications of oral vasodilatory agents and iv prostaglandin analogous. Sympathicotomy was performed on the left hand first and the effects were compared with the contralateral hand after 3 and 12 months. Major exclusion criteria were severe lung involvement or proximal vascular stenosis. The primary end point was Raynaud's Condition Score (RCS) and Quality of life (SF-36). Among others, cooling fingertip plethysmography (PPG) and laser doppler imaging (LDI) were used as secondary end points for objective assessment of hand perfusion. Results: This is an interim report, and 4 patients have been included so far (age 20, 29, 32, 56 years), male/female 3/1, 3 primary, 1 secondary), without a history of digital ulcers. No adverse events have been observed, apart from some hyperaemia in the first post-operative week. RCS significantly in each patient. Additionally, a clear improvement in hand perfusion following cooling was observed with PPG and LDI, as compared to the contralateral site. All 4 patients were satisfied and agreed to have their contralateral site operated on also. Patients will be followed in the outpatient clinic to assess long term efficacy. Conclusions: Single-port thoracoscopic sympathicotomy is a novel minimally-invasive technique which appears to be safe and feasible in patients with treatment resistant Raynaud's phenomenon. However, this study is ongoing and long-term efficacy needs to be established. Disclosure of Interest: None declared